Burkitt lymphoma and cavernous sinus syndrome with breast uptake on 18F-FDG-PET/CT: A case report. Issue 46 (November 2017) - Reyneke, Florette; Mokgoro, Neo; Vorster, Mariza; Sathekge, Mike
Abstract: Rationale: Burkitt lymphoma (BL) is a type of non-Hodgkin lymphoma that arises in the B-cells. Cavernous sinus involvement is rare, especially in adults. Here we report an unusual case of a 30-year-old HIV-positive woman with BL and cavernous sinus syndrome who also had intense bilateral breast uptake, related to menstrual cycle. Fluorine-18 2-fluoro-2-deoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) has been found to be useful in the management of BL. Patient concerns: A 30-year old female patient presented with a history of diplopia and headache. Diagnoses: Magnetic resonance imaging revealed a large cavernous sinus mass. A bone marrow biopsy was done and demonstrated extensive marrow infiltration by Burkitt lymphoma. Further investigation detected the Epstein–Barr virus in her cerebrospinal fluid using qualitative polymerase chain reaction. 18F-FDG PET/CT imaging done revealed a hypermetabolic cavernous sinus mass, conglomerates of enlarged pelvic and para-aortic lymph nodes as well as diffuse bone marrow uptake. Intense bilateral breast uptake was noted coinciding with the start of menses. Interventions: She was started on chemotherapy with adjuvant radiotherapy. Outcomes: After her first cycle of chemotherapy, repeat 18F-FDG PET/CT imaging revealed a marked reduction in the metabolic activity and size of the cavernous sinus mass and conglomerates of lymph nodes. The bone marrow activity was still visualized but less intense compared to the staging PET/CT. Lessons: A cavernous sinus mass will rarely be the primary lesion in Burkitt's Lymphoma. Our case demonstrates the role of 18F-FDG PET/CT in the assessment of such cases to detect other primary areas of disease involvement. It is useful in accurate initial staging and monitoring of treatment response in patients with Burkitt's Lymphoma.